2007
DOI: 10.1159/000102610
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Arginine Kinase, an Allergen from the Shrimp <i>Litopenaeus vannamei</i>

Abstract: Background: Consumption of seafood can produce allergic symptoms in susceptible individuals and crustacean allergies are the most frequently reported causes of allergic reactions. Methods: An allergen from the muscle of the white shrimp Litopenaeus vannamei was purified by ion exchange chromatography and identified by mass spectrometry of tryptic peptides and its specific enzymatic activity. Moreover, the corresponding full-length cDNA was obtained from an L. vannamei muscle cDNA library. Results: A 40-kDa pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
89
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(96 citation statements)
references
References 44 publications
3
89
0
2
Order By: Relevance
“…In a recent study, an arginine kinase has also been identified as a prawn allergen [20,21] . In addition to tropomyosin, the tryptic peptide fragments isolated from the digested 42 kDa of spot 2 is similar to arginine kinase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, an arginine kinase has also been identified as a prawn allergen [20,21] . In addition to tropomyosin, the tryptic peptide fragments isolated from the digested 42 kDa of spot 2 is similar to arginine kinase.…”
Section: Discussionmentioning
confidence: 99%
“…Besides tropomyosin, arginine kinase with a molecular mass of 40 kDa, termed as Pen m 2 [20] and Lit v 2 [21] has also been reported as prawn allergen. Also, arginine kinase has been described as a cross-reacting allergen among crustaceans and between crustaceans and insects [22] .…”
Section: Introductionmentioning
confidence: 99%
“…this protein showed 60% similarity to AK of the crustacean, kuruma prawn (Penaeus japonicas) (Yu et al, 2003). AK was recently reported as an allergen in different crustacean species which was identified in white shrimp (Litopenaeus vannamei) (García-Orozco et al, 2007), gulf shrimp (Penaeus aztecus) (France et al, 1997), chinese shrimp (Fenneropenaeus chinensis) ( Y a o et al, 2005), black tiger prawn (Penaeus monodon) and other shrimp species using a proteomics approach (Abdel Rahman et al, 2010a;Yu et al, 2003). Moreover, AK has been identified in other crab species: mud crab (Scylla serrata) (Shen et al, 2011), and by our group in snow crab (Chionoecetes opilio) (Abdel Rahman et al, 2011), where 49% of the participant patient's sera have a reactivity with AK.…”
Section: Shellfish Allergensmentioning
confidence: 81%
“…Este alérgeno presenta 92 % de identidad en la secuencia de aminoácidos con Lit v 2 y Cra c 2 del camarón Crangon crangon, hecho que podría tener relevancia en la reacción cruzada entre estas especies (43)(44)(45).…”
Section: Arginina-cinasaunclassified